Rethinking Jewishness in Weimar cinema - Hales, Barbara, 1962-; Weinstein, Valerie, 1971- (New York : Berghahn Books, 2021)
"The burgeoning film industry in the Weimar Republic was, among other things, a major site of German-Jewish experience, one that provided a sphere for Jewish "outsiders" to shape mainstream culture. The chapters collected in this volume deploy new historical, theoretical, and methodological approaches to understanding the significant involvement of German Jews in Weimar cinema. Reflecting upon different conceptions of Jewishness - as religion, ethnicity, social role, cultural code, or text - these studies offer a wide-ranging exploration of an often overlooked aspect of German film history"--
Chapter 15 -- "Filmrettung: Save the Past for the Future!": Film Restoration and Jewishness in German and Austrian Silent Cinema -- Afterword -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 03, 2020).
JSTOR
Keywords: Motion pictures -- Germany -- History -- 20th century; Jews in the motion picture industry -- Germany; Jewish motion picture producers and directors -- Germany; Germany -- Civilization -- Jewish influences; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Juifs dans l'industrie cinématographique -- Allemagne; Producteurs et réalisateurs de cinéma juifs -- Allemagne; PERFORMING ARTS / Film & Video / History & Criticism; Civilization -- Jewish influences; Jewish motion picture producers and directors; Jews in the motion picture industry; Motion pictures; Germany; 1900-1999; History